Gambaran Tingkat Pengetahuan Remaja Tentang Pengaruh Merokok Terhadap Kesehatan Gigi dan Mulut Di Kp. Cipadati Kabupaten Bandung (Poltekkes Kemenkes Bandung, 2023)
Smoking is dangerous for health. Smoking is a habit that is often done by people, both at the age of teenagers and adults. Factors behind smoking habits in adolescence are the lack of knowledge of adolescents about the dangers of smoking for health, including dental and oral health. This study aims to determine the level of knowledge of adolescent smokers about the impact of smoking on dental and oral health in Kp. Cipadati RT.03 RW.03 Cinunuk Village, Bandung Regency. This type of research is descriptive by distributing questionnaires. The number of respondents in this study were 32 teenage boys aged 13 to 19 years who smoked and lived in Kp. Cipadati RT.03 RW.01 Cinunuk Village, Bandung Regency. The results of the study from 32 respondents, showed the level of knowledge of adolescents about the effect of smoking on dental and oral health in Kp. Cipadati RT.03 RW.01 Cinunuk Village, Bandung Regency, 50.0% of respondents are in the category of a good level of knowledge, and for knowledge of adolescent smoking prevention efforts for dental and oral health, 40.6% of respondents are in the category of poor knowledge level. Conclusion: the level of knowledge of adolescents is good, but preventive efforts for adolescent smokers are still lacking.